Microstructure and Mechanical Behavior of Multidirectional Forge SIMA Process Al- Si Hypereutectic Alloy - Choudhary I.N.; Sinha N.K.; Mahali M.; Singh J.K. (My University, 2025)
During Strain Induced Melt Activation (SIMA) process, the mechanical and microstructural characteristics of the hypereutectic alloy having composition 16wt.%Si and 20wt.% Si were examined. The strain-induced melt activation (SIMA) procedure involved applying multidirectional forging at 300ºC and then semi-solid treatment for 0 min to 30 min at 580 ± 5 °C. X-ray diffraction (XRD), optical microscopy and scanning electron microscopy (SEM) were used to characterise the phase present before and after casting, microstructures transformation and fracture behaviour analysis. Hardness, density and porosity were also estimated and observed that HT 2 sample having higher hardness (Approx. 72VHN and 85 VHN) and lower density (2.68 g/cc and 2.50 g/cc) as compare to cast and multidirectional forged hypereutectic alloy in both 16wt. %Si and 20wt. % Si composition due to primary Si hard particles having lower density and refinement of eutectic and primary phase refinement. Using tensile tests, the mechanical properties of the cast, multidirectional forged and HT 2 sample were examined. According to the results, samples with refine grain, uniformly distributed having spherical morphology were (treated using SIMA) show the highest tensile strength (103 MPa and 115 MPa) and ductility (8.6% and 6.8%) at 10 min holding in 16wt.%Si and 20wt.% Si hypereutectic alloy. Fracture behaviour analysis reviles that fracture mode moves toward ductile from brittle in both hypereutectic alloy. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.